Distribution of Malocclusion and Occlusal Traits among Tibetan Adolescents residing in Nepal - Karki, Saujanya; Parajuli, Umesh; Kunwar, Nischal; Namgyal, Kunsang; Wangdu, Khamsum (Orthodontic Journal of Nepal, 2014)
Introduction: Malocclusion is the irregularity of teeth and is considered as oral health problem. Though etiology of malocclusion is multifactorial, it has considerable impact on the self esteem and social adjustment of an individual. Objective: To determine the prevalence of malocclusion and to assess the association between Angle classification of malocclusion and occlusal traits. Materials & Method: A cross sectional study was conducted among 138 Tibetan students of grade 8-12 were selected. Students with history of orthodontic treatment were excluded from the study. Data was recorded and analyzed using SPSS 17.0 and chi square test was used to evaluate the association between Angle classification of malocclusion and occlusal traits. Result: The prevalence of malocclusion was found to be Angle’s Class I (52.90%), Angle’s Class II (5.10%) and Angle’s Class III (9.40%). Occlusal traits such as overbite, increased overjet, openbite, crossbite, displacement and hypodontia was found to be 5.79%, 10.8%, 10.86%, 9.42%, 50,72% and 4.34% respectively. Conclusion: The prevalence of malocclusion among Tibetan adolescent was found to be higher. Hence, oral health awareness, preventive procedures and promotional programs need to be more emphasized.